Performance comparison of feature-based and CSCPG models for 3D spine reconstruction. Issue 1 (1st January 2018) - KS, Hareesha; Kumar, Sampath
Abstract: 3D deformity of the spine-like scoliosis is commonly assessed using stereo-radiographic technique. The Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) modelling fail in this case, as they are obtained with the patient in sleeping position. Also, they are associated with heavy cost and radiation hazards. We have developed two models namely, feature-based model and a Combined Stereo-Corresponding Point And Geometric (CSCPG) model for 3D spine reconstruction using biplanar x-rays. The spinal disorder is quantified using two parameters, namely axial vertebral rotation and spinal curvature using both these methods. Their performance is compared by considering Non-Stereo-Corresponding Point (NSCP) model as the gold standard method. The feature-based model is less accurate compared to the CSCPG model. The performance of the feature-based model is also poor in the case of deformity quantification. A statistical significance test is conducted in order to verify its suitability in diagnosis of the spinal disorders. The accuracy of feature-based model can be improved by incorporating additional landmark features from the biplanar radiographs. The proposed CSCPG model has accuracy closer to the gold standard technique and can be used a diagnostic tool for the spinal disorders.